Automatic Android-basedWireless Mesh Networks - Wong, Paul; Varikota, Vijay; Nguyen, Duong; Abukmail, Ahmed (Informatica, 2014)
Android devices are portable, equipped with powerful processors, and can act as both mesh routers and clients through Wi-Fi Direct, making them a suitable platform from which to deploy a wireless mesh network. To allow Android devices to automatically establish and participate in a wireless mesh network, we circumvent two key problems of the Android'sWi-Fi APIs: lack of direct support for ad-hoc networking / many-to-oneWi-Fi Direct connections, andWi-Fi Direct WPS authentication limiting applications to ones which require intermittent user interaction.